Restitusi Terhadap Korban Kekerasan Seksual di LPSK Medan; Analisis Hukum Pidana Dan Hukum Pidana Islam - Mustika, Vina; Iwan (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2024)
Sexual violence, which includes actions that demean or attack an individual's body and reproductive functions, causes profound physical and psychological suffering and hinders victims' access to education and healthcare. Ideally, restitution aims to compensate victims for both material and immaterial losses, as stipulated in Law No. 31 of 2014, Supreme Court Regulation No. 1 of 2022, and Law No. 12 of 2022. However, in practice, many restitution cases are not effectively implemented due to the financial incapacity of the perpetrators. This study uses a juridical-empirical method to evaluate the restitution mechanism at the LPSK Representative Office in Medan and assess the restitution system from the perspectives of Criminal Law and Islamic Criminal Law. The research findings indicate that from the perspective of Criminal Law, the restitution system faces major challenges due to the inability of perpetrators to meet their payment obligations, despite adequate regulations and procedures. From the perspective of Islamic Criminal Law, the restoration of victims' rights, known as mahr mitsil or diyat, offers a restorative approach that can complement the restitution system by emphasizing the perpetrator's responsibility to fairly compensate for the losses. This study highlights the need for adjustments in the restitution procedure and detailed evaluation of the perpetrators' financial capacity to enhance the effectiveness of the restitution system.